2019
DOI: 10.1111/labr.12153
|View full text |Cite
|
Sign up to set email alerts
|

Labor Reallocation, Employment, and Earnings: Vector Autoregression Evidence

Abstract: We present time series evidence for the USA 1993–2013 on the relationship between labor reallocation, employment, and earnings using a vector autoregression framework. We find that an increase in labor market churn by 1 percentage point predicts that employment will increase by 100,000–560,000 jobs, lowering the unemployment rate by 0.05–0.25 percentage points. Job destruction does not predict changes in employment but a 1 percentage point increase in job destruction leads to an increase in unemployment 0.14–0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the study reveals a strong relationship between labor flows and short-term income inequality. Using the same framework, Hyatt and McElroy (2019) analyzed the relationship between labor reallocation, employment and income in the USA between 1993 and 2013. Using an autoregressive vector framework, the authors found that a 1% increase in labor reallocation creates between 100,000 and 560,000 jobs, reducing the unemployment rate by 0.05-0.25 percentage points.…”
Section: The Impact Of Job Reallocation On Unemployment: a Review Of ...mentioning
confidence: 99%
“…Furthermore, the study reveals a strong relationship between labor flows and short-term income inequality. Using the same framework, Hyatt and McElroy (2019) analyzed the relationship between labor reallocation, employment and income in the USA between 1993 and 2013. Using an autoregressive vector framework, the authors found that a 1% increase in labor reallocation creates between 100,000 and 560,000 jobs, reducing the unemployment rate by 0.05-0.25 percentage points.…”
Section: The Impact Of Job Reallocation On Unemployment: a Review Of ...mentioning
confidence: 99%